2021
DOI: 10.1038/s41746-021-00489-2
|View full text |Cite
|
Sign up to set email alerts
|

Privacy-first health research with federated learning

Abstract: Privacy protection is paramount in conducting health research. However, studies often rely on data stored in a centralized repository, where analysis is done with full access to the sensitive underlying content. Recent advances in federated learning enable building complex machine-learned models that are trained in a distributed fashion. These techniques facilitate the calculation of research study endpoints such that private data never leaves a given device or healthcare system. We show—on a diverse set of si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 18 publications
0
43
0
Order By: Relevance
“…In future iterations, once the value of using GPT-3 in the health care setting is assured, the responsibility of accessibility could be delegated to health care and government agencies. Such agencies may distribute the “GPT-3-as-a-Service” platform through secure cloud platforms and establish a federated learning mechanism to run decentralized training services while collaboratively contributing to the GPT-3 model [ 28 ]. This would also reduce the burden on individual health systems when it comes to building, training, and deploying their own GPT-3 platforms and reduce costs.…”
Section: Operational Considerations: Compliance Trust and Accessmentioning
confidence: 99%
“…In future iterations, once the value of using GPT-3 in the health care setting is assured, the responsibility of accessibility could be delegated to health care and government agencies. Such agencies may distribute the “GPT-3-as-a-Service” platform through secure cloud platforms and establish a federated learning mechanism to run decentralized training services while collaboratively contributing to the GPT-3 model [ 28 ]. This would also reduce the burden on individual health systems when it comes to building, training, and deploying their own GPT-3 platforms and reduce costs.…”
Section: Operational Considerations: Compliance Trust and Accessmentioning
confidence: 99%
“…Such countermeasures may be neither desirable nor needed in the presence of proper governance and trusted collaborative relationships between data partners in a DDN. Despite these challenges, recent studies using federated learning with different ML architectures have shown that it is possible to achieve levels of performance comparable to models trained using a centralized approach [ 112 ] and better than locally trained models. For example, in a multi-site study [ 113 ] using structured EHR data (e.g., laboratory data and vital signs) and chest X-ray images to predict the future oxygen requirements of symptomatic patients with COVID-19, the global federated deep learning model, trained using data from 20 clinical sites around the world, outperformed all local models that were trained at a single site using that site’s data (Table 2 ).…”
Section: Challenges and Considerationsmentioning
confidence: 99%
“…11 This approach has enabled collaborative learning for several medical applications, and it has been shown that FL performs comparably with centralized training on medical datasets. 12 , 13 , 14 Recently, the concept of swarm learning (SL) has been proposed; it enables decentralized machine learning for precision medicine. The seminal work of SL 15 is based on edge computing and permissioned blockchains and removes the need for a central server in the FL approach.…”
Section: Introductionmentioning
confidence: 99%